Checklist and typification of Parnassia (Celastraceae) - Shu, Yumin; Yu, Huiying; Mu, Xianyun; Zhang, Zhixiang (Phytotaxa, 2017)
As a precursor of taxonomic revision of genus Parnassia, we present here the most current list of taxa. Parnassia currently has 61 species, 2 subspecies, 11 varieties and 1 forma, 76 synonyms and 8 invalid names, for a total of 159 names (autonyms not counted). Lectotypes are designated for 24 names and the correct author citation of P. ornata is formalized.